Multifunctionality of the Lithuanian tada and English then in spoken discourse: a cross-linguistic analysis - Makauskaitė, Indrė (Kalbotyra, 2017)
The present study examines the multifunctionality of the Lithuanian tada and the corresponding English then. The aim of the analysis is to compare their semantic and functional behaviour in spoken discourse. In English and Lithuanian dictionaries, the meanings of tada and then differ: Lithuanian dictionaries only provide definitions related to time and result, whereas English dictionaries offer a few pragmatic meanings alongside the meanings of time and result. This raises the question of whether the Lithuanian adverbial tada possesses any pragmatic meanings. Several studies have closely analysed then as both a temporal adverbial and as a discourse marker but there have been no studies to date of tada as a discourse marker. The process of a predication adverbial turning into a sentence adverbial and then into a discourse marker is common in many languages and, as such, this transformation may be considered universal. One of the aims of the paper is to verify if this adverbial cline exists in the Lithuanian language. The analysis is corpus-based and the data are obtained from the Corpus of the Contemporary Lithuanian Language and the British National Corpus.
Keywords: temporal adverbial; discourse marker; spoken discourse; temporal deixis; corpus linguistics; cross-linguistic analysis; adverbialisation